Learning pronunciation components using u-dictionary application for a university student - Yolanda Aprilia; Yousef Bani Ahmad (Politeknik Negeri Bali, 2020)
The topic of this study is about the use of U-Dictionary application in learning pronunciation components to the high-level student in intelligibility principles in order to get an understandable conversation in speaking practice. The research questions are asking about the way of using the U-Dictionary application in assisting a student in learning pronunciation components and how are her responses based on the tripartite model from Rosenberg and Havland (1960); affect, behavior, and cognition. The participant is a student in the fourth semester of university in Karawang and the data has been collected by an interview based on the Narrative Inquiry method from Clandinin and Connelly (2000). The finding showed that the application can assist her in learning pronunciation components especially for segmental features such as vowel and consonant and supra-segmental ones in intonation. In short, the U-Dictionary Application can help a student in learning pronunciation components even for supra-segmental features only one aspect existed.